2014
DOI: 10.1038/mi.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-related apoptosis-inducing ligand mediates the resolution of allergic airway inflammation induced by chronic allergen inhalation

Abstract: Allergic asthma can vanish over time either spontaneously or induced by allergen-specific immunotherapy. In mice with established airway allergic inflammation, chronic intranasal (IN) allergen challenges decreases progressively airway allergic inflammation. Here we compared the contribution of different regulatory pathways that could be associated with this phenomenon, known as local inhalational tolerance. We found that inhalational tolerance was not associated with increased number of regulatory T cells or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…However, there may also be a harmful relationship between levels of TRAIL and vascular inflammation and atherosclerosis, and this requires further investigation [ 29 ]. Similarly, while some authors report a potential involvement of endogenous TRAIL in the development of allergic asthma in preclinical models [ 30 ], we, among others, have shown that soluble exogenous TRAIL appears to play a protective role in the resolution phase of asthma in a model of chronic allergen inhalation [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 61%
“…However, there may also be a harmful relationship between levels of TRAIL and vascular inflammation and atherosclerosis, and this requires further investigation [ 29 ]. Similarly, while some authors report a potential involvement of endogenous TRAIL in the development of allergic asthma in preclinical models [ 30 ], we, among others, have shown that soluble exogenous TRAIL appears to play a protective role in the resolution phase of asthma in a model of chronic allergen inhalation [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 61%
“…It is now well recognized that resolution of inflammation is a key step for dampening the inflammatory response and is instrumental for regaining homeostasis . Resolution of inflammation has been considered an active and complex process associated with the induction of a proresolving programme, which includes the downregulation of leukocyte survival, production of proresolving mediators , cessation of the recruitment and effector activity of granulocytes, and clearance of apoptotic cells by efferocytosis .…”
Section: Introductionmentioning
confidence: 99%
“…We [3] and others [47] have demonstrated that long term, continuous exposure to an allergen can result in tolerance development and ultimate resolution of allergic airway disease (AAD) in a variety of murine models. Although previous investigations in long-term models of ovalbumin (OVA)-induced AAD have added tremendously to our knowledge of the tolerogenic mechanisms utilized by the mucosal immune system to suppress allergic inflammation, OVA is far less structurally and immunologically complex than the majority of human allergens [8].…”
Section: Introductionmentioning
confidence: 99%